Models for a Post-COVID US foreign economic policy (2020)
The COVID-19 pandemic has intensified centrifugal forces in the global economic order, forces which have been growing in strength over recent years. The crisis has animated governments to impose sweeping new restrictions on the movement of people and goods, and many of these are likely to remain well after it has passed. More than 70% of the world’s air, sea, and land ports of entry restrict access to foreigners. In the United States, politicians from both major parties are demanding new “Buy American” rules for government health spending. French President Emmanuel Macron is seeking “full independence” in critical medical supplies by year’s-end. Almost ninety countries are now blocking the export of medical goods. Twenty-nine are doing so with food.